Social media and politics: contestation, mediation and civil society - Afouxenidis, Alex (The Greek Review of Social Research, 2015)
In this special issue we consider various perspectives and ideas underlying the current ever-changing political and digital environments. There have been a substantial number of theories, coupled by empirical research over the past few years, on the nature of political behavior with respect to the increased use of the Internet. The main aim of this edition is to explore a few aspects of ‘digital politics’ and what they may mean for contemporary democratic culture. This paper synthesizes and reflects upon concepts presented in the following articles and discusses some recent developments and debates related to the dynamics of the online world.